(untitled) (Research, Society and Development, 2022)
Acute cholecystitis is an inflammatory pathological process of the gallbladder resulting from acute obstruction of the cystic duct. Although it is more frequent in females, the number of male patients increases with advancing age, reaching 30% of cases over 65 years of age. It presents as a surgical emergency and usually requires hospitalization for treatment. It is associated with significant morbidity and mortality, especially in elderly patients. The most frequent cause is lithiasis, responsible for 90% of cases. In the differential diagnosis of acute cholecystitis, inflammatory or non-inflammatory diseases with expression located in the upper right hemiabdomen must be considered. They are: right-based pneumonia, hepatitis, pyelonephritis, and even myocardial ischemia or infarction. Other diseases of the digestive tract should be kept in mind, such as acute appendicitis of subhepatic location, complicated peptic ulcer and acute pancreatitis. Imaging of the gallbladder and bile ducts has changed dramatically in the last 20 years. The replacement of transparietal cholangiography and oral cholecystography by modern, non-invasive techniques has brought great advances in the diagnosis of diseases of the bile ducts. Currently, the diagnosis and imaging follow-up of biliary diseases is based on ultrasound (US), computed tomography (CT), magnetic resonance imaging (MRI) and scintigraphy. US remains the test of choice in the initial evaluation of acute biliary diseases, due to its ease of performance, wide availability and high accuracy in the diagnosis of acute cholecystitis.